Torrefaction of Municipal Solid Waste in Malaysia - Noor Asma Fazli, Abdul Samad; Nur Ashikin, Jamin; Suriyati, Saleh (Elsevier Ltd, 2017)
Municipal solid waste (MSW) disposal is one of the main issues towards sustainable development in Malaysia. Current practices for MSW disposal such as landfilling and incineration poses a serious problems on the environment and health. Therefore a significant efforts have been made to utilize MSW for energy source by employing gasification process. However, the MSW is characterized by its high moisture content and low high heating value (HHV) which lowering the energy efficiency. In order to overcome this problems, torrefaction can be used as pretreatment method to remove the moisture content and upgrading MSW properties. The objective of this work is to study the effects of torrefaction temperatures ranging from 240 to 330°C for residence time of 30 minutes on two types of MSW namely food waste and wood waste. The torrefied MSWs are characterized in terms of ultimate analysis, proximate analysis and HHV. The mass and energy yields are also performed for both MSW. Based on the torrefaction, it was found that both food waste and wood waste show an increment on the weight percentage of C contents and decrement on the weight percentage of H and O content which resulting into reduce O/C ratio as the temperature is increased. The HHV for both food waste and wood waste are also increased after torrefaction between 240 and 330°C. The mass yield and energy yield were found to decrease with an increase in the torrefaction temperature. This suggests that torrefaction can be used as an effective MSW pretreatment and the torrefied MSW is more suitable to be used as fuel in gasification process.